Psychology - Davis, Stephen F.; Palladino, Joseph J. (Upper Saddle River, N.J. Pearson/Prentice Hall, 2004)
Psychology, research, and you; Behavioral neuroscience; Sensation and perception; States of consciousness...
Taken from Psychology, fourth ed.
Includes bibliographical references (p. 708-737) and index.
Keywords: Psychology -- Textbooks; Tâm lý